THU0661 Osteoporosis screening, primary prevention, and treatment in glucocorticoid treated individuals with rheumatologic disease. (12th June 2018) - Onkka, P.; Khandelwal, S.; Shakoor, N.; Block, J.; Fogg, L.
Abstract : Background: Glucocorticoids are commonly used in a wide variety of inflammatory conditions treated by rheumatologists. Bone loss from glucocorticoids is known to occur early and with relatively small doses. The American College of Rheumatology outlines that Glucocorticoid-Induced Osteoporosis (GIOP) is under screened and undertreated. The ACR guidelines suggest standard clinical care to obtain a baseline DEXA in any individual with anticipated long-term steroid use, primary prevention with calcium, and vitamin D initiation and medical therapy when appropriate based on fracture risk assessments. Objectives: The objective of this study was to determine how successfully the ACR GIOP guidelines are implemented in daily rheumatologic practice. The study investigates the prevalence of osteoporosis screening, prevention, and treatment in patients with rheumatologic diseases over a 2 year period at a large medical centre. Methods: A retrospective cohort study of patients who received rheumatology care between 2014 and 2015 at a large medical centre was performed. Patients were included if they were older than 18 years of age, had a diagnosis of rheumatoid arthritis, systemic lupus, vasculitis, polymyalgia rheumatica, or gout and were receiving ≥5 mg prednisone daily for ≥90 days. Electronic medical records were reviewed and medication history was evaluated. Screening was defined as bone mineral density testing with DEXA within one year of glucocorticoid initiation. Primary prevention and treatment were derived from ACR GIOP criteria and included the initiation of appropriate doses of calcium and vitamin D and initiation of medical therapy to prevent bone loss. The prevalence of screening and treatment was assessed and the relationships with age, gender, and ethnicity were evaluated using Chi Squared analyses and independent samples t-tests. Results: Of the 600 patients reviewed, 61 met criteria of new long-term glucocorticoid initiations. Overall 61% received BMD testing and 48% received osteoporosis primary prevention. Of those who qualified for treatment by ACR GIOP criteria, only 19% received treatment. Patients who received a baseline DEXA were older than those who did not (65±15 vs 57±16 years, p=0.046). Age did not influence treatment. More women compared to men received screening DEXA (68% F vs 41% M, p=0.053) and primary prevention (55% F vs 29% M, p=0.078). Patients who received a longer duration of steroid treatment were more likely to receive primary prevention (16±10 months vs 10±8 months, p=0.015). There was no association between ethnicity or disease status on screening, prevention, or treatment. Conclusions: Glucocorticoid-induced osteoporosis in the setting of a rheumatology practice is a common and manageable condition that should be screened, prevented, and treated. These results from one large academic medical centre in the United States suggest that rheumatologists may not be following ACR guidelines for the assessment and management of patients on chronic steroids. Quality improvement initiatives may be necessary in order provide optimal care for patients. References: [1] Grossman J, et al. American College of Rheumatology2010Recommendations for the Prevention and Treatment of Glucocorticoid-Induced Osteoporosis. [2] Buckley L, et al. 2017American College of Rheumatology Guideline for the Prevention and Treatment of Glucocorticoid-Induced Osteoporosis. Disclosure of Interest: None declared